2017
DOI: 10.5114/aoms.2016.63599
|View full text |Cite
|
Sign up to set email alerts
|

Can coffee consumption lower the risk of Alzheimer’s disease and Parkinson’s disease? A literature review

Abstract: In light of the fact that the number of elderly citizens in society is steadily increasing, the search for dietary factors which might prolong mental agility is growing in significance. Coffee, together with its main ingredient, caffeine, has been the focus of much attention from various researchers, as data on its beneficial effects on human health continue to accumulate. Most reports indicate that moderate coffee consumption may in fact lower the risk for common neurodegenerative conditions, i.e. Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 71 publications
1
30
1
2
Order By: Relevance
“…We observed reduced current coffee intake in our cohort of PD patients as well as reduced current alcohol consumption, in agreement with previous reports. Although coffee and caffeine are known to have potent neuroprotective and anti-inflammatory properties, 57 this study found only a minimal effect of alcohol and coffee consumption on levels of stool immune mediators, with coffee intake inversely associated with IL-6 levels. We found no differences between PD patients and controls in smoking history, but we did observe that having smoked at least 100 cigarettes reduced levels of multiple immune factors in stool.…”
Section: H O U S E R E T a Lcontrasting
confidence: 68%
See 1 more Smart Citation
“…We observed reduced current coffee intake in our cohort of PD patients as well as reduced current alcohol consumption, in agreement with previous reports. Although coffee and caffeine are known to have potent neuroprotective and anti-inflammatory properties, 57 this study found only a minimal effect of alcohol and coffee consumption on levels of stool immune mediators, with coffee intake inversely associated with IL-6 levels. We found no differences between PD patients and controls in smoking history, but we did observe that having smoked at least 100 cigarettes reduced levels of multiple immune factors in stool.…”
Section: H O U S E R E T a Lcontrasting
confidence: 68%
“…Coffee and alcohol consumption and smoking are all reportedly reduced in PD patients, but whether these findings indicate protective effects of these practices, disease‐associated suppression of psychological reward mechanisms, or simply reduced fluid intake because of dysphagia in advanced disease remains undetermined. We observed reduced current coffee intake in our cohort of PD patients as well as reduced current alcohol consumption, in agreement with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…it mainly by the death of dopamine-producing neurons in our brain [86][87][88][89][90][91] Coffee consumption protects against 65 or more aged people from Alzheimer's disease and dementia. It lower 65% risk of Alzheimer's disease…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…The neurodegenerative disease most common in old people over 65 years of age and above [64,89,[91][92][93] [32, 61,[94][95][96][97][98][99][100][101] Coffee consumption can lower about 26% probability of colorectal cancer, especially distal colon cancer. It is known as a healthy beverage for the prevention of colorectal cancer.…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…This indicates that moderate consumption of caffeine can affect cognition [8]. Coffee and tea consumption has been studied extensively to determine the long-term effects of consumption and the associations with numerous diseases such as diabetes, hypertension, Alzheimer's disease, and dementia [9][10][11][12]. Most previous studies have also only used behavioral performance and self-reported measures to understand the effects of consumption on cognition.…”
Section: Introductionmentioning
confidence: 99%